Fabrication of silicon nanopillar arrays by electron beam lithography and reactive ion etching for advanced bacterial adhesion studies. (13th March 2019) - Doll, P W; Al-Ahmad, A; Bacher, A; Muslija, A; Thelen, R; Hahn, L; Ahrens, R; Spindler, B; Guber, A E
Abstract: Within this work we demonstrate the fabrication of silicon nanopillar arrays for advanced cell/surface interaction studies and the results of the bacterial interaction of Escherichia coli with such highly ordered nanostructures. By combination of Electron Beam Lithography and Reactive Ion Etching a powerful and highly precise method for the fabrication of nanopillars with different diameters in the sub 100 nm region and high aspect ratios is available. The fabrication method allows building highly ordered nanotopographies which can help to increase the understanding of cell/substrate interaction. The biological results indicate that the adhesion of E. coli correlates to the available discrete adhesion bond points on top of the pillars and additionally that the cells align with the nanostructures to maximize their contact to the surface. The research of such structures will lead to the development of novel materials which might reduce biomaterial associated infections.